Using Fairy Tales To Increase Primary Class Students' Vocabulary - Surmakhon Ismailova (Genius Journals, 2023)
In the article, we should introduce the young generation to become a perfect person, strive for sophistication and beauty, feel it and enjoy this process, appreciate national artistic values and feel that it is personal responsibility to pass it on to the next generation. It has been shown that the way to raise this perfect person and activate them in the educational process is one of the urgent issues that must be resolved.
Keywords: proverb; fairy tale; quick telling; riddle